HYGIENIC ASSESSMENT OF NATURAL AND ARTIFICIAL ILLUMINATION IN MECHANICAL PROCESSING WORKSHOPS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In mechanical processing workshops, the efficiency of labor processes and workers’ health largely depend on environmental factors, including illumination levels. This literature review analyzes the hygienic significance of natural and artificial lighting, their compliance with regulatory requirements in mechanical processing operations, and their impact on the activity of the visual analyzer. Based on statistical and experimental data presented by the World Health Organization (WHO), the International Labour Organization (ILO), and leading scientific sources in industrial hygiene, it has been scientifically substantiated that insufficient illumination increases the risk of visual fatigue, occupational injuries, and production errors. The literature analysis demonstrates that combined (natural + artificial) lighting systems represent the most hygienically optimal solution for mechanical workshops.